Impact of the War in Ukraine on the Ability of Children to Recognize Basic Emotions - Oleksandra Loshenko; Petr Palíšek; Ondřej Straka; Michal Jabůrek; Šárka Portešová; Anna Ševčíková (Frontiers Media S.A., 2024)
ObjectivesThis study assessed emotion recognition skills in school-age children in wartime conditions in Ukraine.MethodsAn online survey based on the concept of basic emotions was administrated to a sample of 419 schoolchildren from Ukraine and a control group of 310 schoolchildren from the Czech Republic, aged 8 to 12.ResultsThere is no difference in judging the intensity of anger and fear by Ukrainian children, compared with the control group. There is no evidence that the emotions of anger, fear, and sadness were better recognized in the Ukrainian group. Children from Ukraine were better at recognizing positive emotions than Czech children.ConclusionIncreased risks of threats and wartime experience do not impair the accuracy of identification of emotions like fear or the assessment of intensity of basic emotions by children who experience war in Ukraine. Still, it is important to continue studying the long-term consequences of military conflicts in order to deepen the understanding of their impact on human mental functioning.